HUBUNGAN DAYA LEDAK OTOT TUNGKAI DAN KOORDINASI MATA-KAKI DENGAN KEMAMPUAN TENDANGAN KE GAWANG TIM SMAN 2 BANGKO KECAMATAN BANGKO - ', Husni; ', Ramadi; Agust, Kristi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT, The background of the problem in this research is not maximal shooting the goal ability of being owned by a team of SMAN 1 Bangko. From several opportunities to shooting, only slightly leading into the opposing goal. This problem is evident from observations of researchers at the time of the trial and the game, it is suspected because of explosive power leg muscles and eye-foot coordination owned by the player. Therefore, the purpose of this study was to determine whether there is a corelation of explosive power leg muscle and eye-foot coordination with the shooting the goal ability team SMAN 1 Bangko. This type of research is correlational comparing the measurement results of two different variables in order to determine the degree of correlation between these variables. As independent variables (X1) is explosive power leg muscles, (X2) eye-foot coordination, while the dependent variable (Y) is shooting into goal ability. The research data was obtained from the results of tests using a standing broad jump test, and test coordination and shots on goal test. The sample in this study is a soccer player team SMAN 1 Bangko amounting to 24 people (total sampling). Based on the research results can be concluded as follows: There is a significant corelation (significant) between the explosive power leg muscles with shooting the goal ability Soccer Team SMAN 1 Bangko District Bangko marked with 0429 count r> r-0404 tab. There corealtion meaningful (significant) between the eye-foot coordination with shooting the goal Soccer Team SMAN 1 Bangko District Bangko marked with 0578 count r> r-0404 tab. There is a significant corelation (significant) between the variables of explosive power leg muscles and eye-foot coordination together with shooting the goal ability Soccer Team SMAN 1 Bangko District Bangko obtained 0580 count r> r-tab 0.404Fhitung 5,332> Ftabel 3:47 then HO HA rejected and accepted.Keywords : Explosive Power, Legs Muscles, Eye-Foot Koordination, Shooting Soccer